2021
DOI: 10.1177/10575677211020813
|View full text |Cite
|
Sign up to set email alerts
|

Representations of Policing Problems and Body-Worn Cameras in Existing Research

Abstract: In this article, we analyze scholarly publications on body-worn cameras (BWCs) to shed light on scholars’ grounding assumptions about BWC technology and the policing problems assumed to be amended by it. We conducted a systematic search and a double-blind review, including 90 peer-reviewed journal articles, and analyzed how scholars warrant their studies, their findings and their recommendations. We found that BWC research largely investigates the effectiveness of BWCs worn by police officers in the United Sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 119 publications
0
8
0
Order By: Relevance
“…The organizational narrative of the vulnerable officer and the caring employer is firmly established in Sweden, in contrast to the USA, where BWC use in policing was primarily motivated by a desire to control officers, hold them accountable for their actions, and reprimand them for alleged misbehavior (see also Backman and Hansen L€ ofstrand, 2021).…”
Section: Concluding Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The organizational narrative of the vulnerable officer and the caring employer is firmly established in Sweden, in contrast to the USA, where BWC use in policing was primarily motivated by a desire to control officers, hold them accountable for their actions, and reprimand them for alleged misbehavior (see also Backman and Hansen L€ ofstrand, 2021).…”
Section: Concluding Discussionmentioning
confidence: 99%
“…Implicitly, the head of security disavows practices involving BWC use to surveil and control the work of employees. A systematic research review on BWCs has shown that a surveillance-as-control discourse has been prominent in policies, practices and research about implementation and evaluation of BWCs (Backman and Hansen L€ ofstrand, 2021). In UK and USA environments BWC recordings are used to evaluate and reprimand officers for their actions (see, e.g.…”
Section: Qrom 175mentioning
confidence: 99%
See 3 more Smart Citations